Analysis of the Banco de la República's international reserves and Colombia's confidence in the International Monetary Fund (2020)
Alan abroad controlled under the monetary authority of the Banco República, in order to protect the economy against the unfavorable effects of the exchange rate, economic crisis or political problems in the region. Having international reserves in a country allows to improve debt conditions abroad and also allows confidence in the country. The Banco de la República invests in international reserves taking into account what the constitution dictates, as well as law 31 of 1992 determines and the guidelines issued by the IMF, based on the above and taking into account these three fundamental criteria: security, liquidity and profitability, Banco de la República carries out the corresponding credit and monetary interventions both in the country and in foreign investment. However, the purpose of this document is to carry out an analysis of the management that the international reserves have executed and the confidence that this generates in the country, within the framework on which the management and comparability that during the period 2015 - 2019 represents for the country.